PENGARUH BANTUAN PROGRAM STIMULUS EKONOMI TERHADAP PENDAPATAN USAHA (Studi Pada Pelaku UMKM di Kabupaten Sumbawa) - Elly Karmeli; Andi Saputra; Roos Nana Sucihati (Jurnal Ekonomi & Bisnis, 2022)
This study aims to determine the effect of economic stimulus program funding on the income of micro, small and medium enterprises (UMKM) in Sumbawa Regency. This type of research is associative research which is used to determine the relationship between variables and how the level of dependence between the independent variables and the dependent variable. The variables that will be studied in this study are the economic stimulus program assistance funds as the independent variable, and the income of UMKM entrepreneurs in Sumbawa Regency as the dependent variable. The type of data used is quantitative data collected directly from the source through questionnaires distributed to research respondents. Respondents used as data sources amounted to 60 people. Researchers use a questionnaire or questionnaire to collect data. The data that has been collected will then be processed using the SPSS program to be studied using techniques that include simple linear regression analysis, individual parameter hypothesis testing (t test), and determinant coefficient test (R2). The results of this study indicate that the economic stimulus program has a positive and significant effect on the income of UMKM business actors in Sumbawa Regency. The ability of the economic stimulus program to influence variations in changes in the income of UMKM business actors in Sumbawa Regency is 96.2%, while the remaining 3.8% is influenced by other variables beyond the scope of this research, such as the level of education of business actors, type of business, consumer demand, and others.